Explanation:
As the given chemical reaction equation is as follows.
[tex]Mg(s) + Cr^{3+}(aq) \rightarrow Mg^{2+}(aq) + Cr(s)[/tex]
Hence, the oxidation and reduction-half reactions will be as follows.
Oxidation-half reaction: [tex]Mg(s) \rightarrow Mg^{2+} + 2e^{-}[/tex] .....(1)
Reduction-half reaction: [tex]Cr^{3+}(aq) + 3e^{-} \rightarrow Cr(s)[/tex] ....(2)
So, in order to balance the oxidation and reduction half reactions, we multiply equation (1) by 3 and multiply equation (2) by 2.
Therefore, the balanced oxidation and reduction half reactions will be as follows.
Oxidation-half reaction: [tex]3Mg(s) \rightarrow 3Mg^{2+} + 6e^{-}[/tex]
Reduction-half reaction: [tex]2Cr^{3+}(aq) + 6e^{-} \rightarrow 2Cr(s)[/tex]
Thus, we can conclude that the overall balanced reaction equation will be as follows:
[tex]3Mg(s) + 2Cr^{3+}(aq) \rightarrow 3Mg^{2+}(aq) + 2Cr(s)[/tex]